Protest movements and the Bulgarian parliamentary elections of 2013–2014 - Sayfutdinova, Leyla; Stoyanov, Dragomir (Socio.hu Társadalomtudományi Szemle, 2017)
In 2013, Bulgaria’s political system was shaken to its core by an unprecedented wave of mass protests. The protests, which began with dissatisfaction over the government’s policy towards household electricity bills, brought down the government and led to new elections in June 2013. But after the new government was formed, a new wave of protests began. The renewed protest movement demanded transparency and accountability. Under the slogan ’Who?’, the movement protested against corruption by the new government, and demanded to know who was governing the country ’behind the scenes’. Political developments in Europe and beyond have demonstrated links between protests and the rise of populist parties. Yet, the Bulgarian case stands apart from these developments. In Bulgaria, the protest movement and the populist parties remain disconnected from each other; the agenda of populist parties does not correspond with the demands of the protest movement. In this paper, we attempt to investigate why this is the case. We argue that the disjuncture between the protest movement and the populist parties in Bulgaria can be explained by the increasing polarization of Bulgarian society. The protest movement represents the proEuropean and pro–democratic part of the electorate; the nationalist populist parties that entered parliament appeal to the euro–sceptic and socially conservative part of society, and ultimately those who hope for a restoration of social order through a ’strong hand’ and authoritarian rule. The paper is based on the analysis of secondary qualitative and quantitative materials. Keywords: Bulgaria, #DANSwithme, political parties, populism, protests